"Tapwaroro is true": Indigenous Voice and the Heteroglossia of Methodist Missionary Translation in British New Guinea. (December 2016) - Schram, Ryan
Abstract : In the semiotic ideology of many Christian discursive practices, it is assumed that any language can convey the same message of salvation, and any person is capable of true belief, no matter how it is expressed. Evangelism, especially by Western missions, thus centers on translating Christian texts into vernacular languages. This article considers these understandings and practices by examining the written discourse of Australian Methodist missionaries in the early colonial period in New Guinea. These missionaries desired an encounter with heathens in an unevangelized field, but they operated in a colonial terrain defined by the politics of past encounters between Australians and Melanesians. In their writings, missionary authors parody the voices of indigenous speakers and present a world in which missionary and native cannot arrive at a shared understanding of religion. Their parody usually involves quoting one term, taparoro, as a word used by natives for the mission and its activities. Having presented a world defined by a persistent gap in understanding, missionaries appropriate this particular sign of their own otherness to others as a basis for a new mission register into which they can translate Christian ideas. In so doing, they do not simply impose one dominant code as a metalinguistic standard, but fashion a new discourse out of available materials in a complex field of interlingualism.